Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Pelayanan Pasien diinstalasi Farmasi RSUD Rantauprapat - Sri Lestari Ramadhani Nasution; Dewi Purwanti; Ermi Girsang (STIKes Hang Tuah Pekanbaru, 2021)
The problem found was that the patient waiting time for prescription services exceeded the standard set by the government for non-concoction drugs less than 30 minutes and concoctions for drugs less than 60 minutes, namely for non-concoctions for 39 minutes and concoctions for 60.4 minutes. While the factors that influence the waiting time for drug services include the absence of a drug vacancy during the service, there are still doctors who have not been guided by the list books and drug price ceilings, so that officials must reconfirm, and there are officers who have not worked on prescriptions because they are still doing activities or prescriptions other. The purpose of this study was to determine the factors that influence patient satisfaction in the Pharmacy Installation at Rantauprapat District Hospital. The sample in this study was a number of 35 outpatients in the pharmaceutical installation with 35 people using a purposive sampling technique. Based on the results of the study it can be concluded that there is an influence of waiting time with patient satisfaction. There is an influence of information on patient satisfaction. There is an influence of human resources with patient satisfaction. There is an influence of facilities infrastructure with patient satisfaction. There is an influence of satisfaction on improving patient performance. The most dominant variable in this study is the X4 variable, namely the role of information.Â